Pembentukan Karakter Religius Anak Melalui Aktivitas Keagamaan dalam Kegiatan Pengabdian Masyarakat di Desa Sumber Padi DSN V - Armayanti Nasution, Raisah; Amalia Hasibuan, Afwany; Puspita Lubis, Bella; Nadia, Elsya; Alifah Hani, Najwa; Adewiya, Rabiatul (UIN Fatmawati Sukarno Bengkulu, 2025)
Character education plays a crucial role in helping children develop good morals, strong faith, and a sense of piety. Given current global challenges, building religious character from an early age is becoming increasingly important. This study examines how religious activities help shape the religious character of children in Sumber Padi Village, Hamlet V. The study employed qualitative methods with a focus on fieldwork. Data were collected through observation and recording, then analyzed using the Miles and Huberman model, which includes data reduction, clear presentation, and accuracy checking. The results show that children's religious character is formed through routine religious activities such as congregational prayer, reading the Quran, celebrating religious holidays, studying Islam, and working together with others. These activities instill religious values such as discipline, cleanliness, honesty, sincerity, tolerance, mutual assistance, and politeness. Children exhibited positive behavioral changes, such as increased social awareness, worship habits, and courage and confidence in appearing in public spaces.